If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8 + 8 = -4(2x + -4) Combine like terms: 8 + 8 = 16 16 = -4(2x + -4) Reorder the terms: 16 = -4(-4 + 2x) 16 = (-4 * -4 + 2x * -4) 16 = (16 + -8x) Add '-16' to each side of the equation. 16 + -16 = 16 + -16 + -8x Combine like terms: 16 + -16 = 0 0 = 16 + -16 + -8x Combine like terms: 16 + -16 = 0 0 = 0 + -8x 0 = -8x Solving 0 = -8x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '8x' to each side of the equation. 0 + 8x = -8x + 8x Remove the zero: 8x = -8x + 8x Combine like terms: -8x + 8x = 0 8x = 0 Divide each side by '8'. x = 0 Simplifying x = 0
| -8(n-7)=-7n-2 | | -8(n-7)=7n-2 | | 0.07y+0.09(100-y)=7.6 | | (V+5)(v-3)=x | | 9=t/2 | | 4t+6=5t+1 | | .3074= | | 74-6-t=25 | | .1523= | | .0789= | | 2-5/(3x-7)=2 | | t-8-4=31 | | 1.571428n=44 | | X=-16x^2+80x+0 | | 5y-19=2y+8 | | log(5x)-38=-28 | | 4b-6=6b | | -8(x-5)+2=-7x+7 | | 9x=(27/9)*6 | | 7(x+5)=8x+6 | | (23-3y)/(y-6) | | 9y-2=38+y | | 13x-(3x+12)-12x=-5x+3 | | -2(-3-x)=7 | | 2/3=x/25-x | | 13=2w+3(w+6) | | 6x+4=-28-2x | | -7v+5(v-3)=-23 | | 3x+19=3x-103 | | 12-t+25=23 | | 4*9-5y=26 | | G-5.2=-18.73 |